DATIV—Remote Enhancement of Smart Aerosol Measurement System Using Raspberry Pi-Based Distributed Sensors - Hasanuzzaman, Gazi; Buchwald, Tom; Schunk, Christoph; Egbers, Christoph; Schröder, Andreas; Hampel, Uwe (Sensors (Basel, Switzerland), 2024)
Enclosed public spaces are hotspots for airborne disease transmission. To measure and maintain indoor air quality in terms of airborne transmission, an open source, low cost and distributed array of particulate matter sensors was developed and named Dynamic Aerosol Transport for Indoor Ventilation, or DATIV, system. This system can use multiple particulate matter sensors (PMSs) simultaneously and can be remotely controlled using a Raspberry Pi-based operating system. The data acquisition system can be easily operated using the GUI within any common browser installed on a remote device such as a PC or smartphone with a corresponding IP address. The software architecture and validation measurements are presented together with possible future developments.